Influence of source and conditions of peat accumulation on composition of peat bitumen from two fen mires of Western Siberia - Olga Serebrennikova; Eugenia Strelnikova; Yulia Preis; Maria Duchko (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the work is determined by the necessity to obtain data on the organic matter composition of different kinds of peat, on its transformation ways during diagenesis in connection with the possible use of peat as an alternative hydrocarbon source and as a potential precursor of coal and oil in the field of geological research. The main aim of the study is to characterize the features of bitumen compounds composition of peat samples formed in the swamps of different terrestrial plant communities and the peat deposit environment. Methods: chromatography-mass spectrometry. Results: The authors have determined the differences and similarities in the extracts organic compounds composition of fen woody peat, which has been accumulated in acidic (swamp Temnoye) and alkaline (swamp Kirek) conditions. The homologues C23, C25, C27 and C29 dominate among n-alkanes in all the samples with a maximum on C27. The close composition is fixed for n-alkane-2-ones. Palmitic acid dominates among fatty acids, myristic and lauric acids are also presented in high concentrations. The derivatives of lupene, oleanene, hopane and hopene, among diterpenoids - naphthenic, naphthenoaromatic and aromatic hydrocarbons, formed as a result of abietic acid and its monoaromatic analogue conversion, and also labdenes were detected among triterpenoids. Steroids are presented by sterols, stanols, stanones and stenones. Fen peat deposited in a medium with higher pH values is characterized by reduced biomarkers content with a higher ratio of steroids to triterpenoids. Alkaline conditions of organic matter accumulation and transformation through diagenesis contribute to the conservation of peat acyclic and cyclic acids, preventing their esterification. Such conditions also promote sterols preservation, limiting their transformation into stenones and stanones. Acidic conditions contribute active esterification especially of cyclic acids and the formation of triterpenoids keto-derivatives. It promotes as well the hydrogenation of unsaturated tricyclic structures. With increasing conifer content in the original plant biomass the content of sesqui- and diterpenoids sharply rises, the concentrations of tocopherols, phytol and its derivatives, C23 and C25 homologues of n-alkanes and n-alkan-2-ones increases, the relative content of palmitic acid and its ethyl ester high molecular homologues decreases, cholesterol derivatives, triterpene and steroid alcohols fully disappear.